Proposing Peace Agreement Ratification Procedures in Delay of Debt Payment Obligations (PKPU) - Nainggolan, Bernard (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2023)
Peace agreement in Delay of Debt Payment Obligations (PKPU) offers ways to pay all or part of the debt as an effort to avoid bankruptcy, so that the peace is legally valid and binding on the parties, it requires ratification of the peace from the Commercial Court. However, in practice, it was found that there were delays in ratifying the peace agreement that had been agreed to by the parties due to reports that had not been submitted by the management during the PKPU period. The focus of the research is to identify the legal consequences of delaying the approval of the peace agreement on debt settlement of the debtor. The method used is normative juridical with descriptive analysis. Secondary data sources are used, involving legal materials related to primary legal materials and providing explanations for them. Secondary data sources include books, journals, papers, reports, scientific papers, and undergraduate research results in the field of law. Apart from that, tertiary legal materials are also used as additional references, such as articles, books or papers. The results of the research show that delays in ratifying peace agreements that violate statutory provisions have the potential to create legal uncertainty and can lead to debtor bankruptcy. The research conclusion emphasizes the importance of maintaining compliance with legal procedures in PKPU in order to achieve legal certainty for all related parties.